Ok...I considered it....oh..u want me to answer it...lol..ok
5/6(1/2x + 6) - 3x
5/12x + 30/6 - 3x
5/12x - 36/12x + 5
- 31/12x + 5 <===
I'm guessing on the make up of the matrices.
First off let's look at [C][F].
[C]=
[F]=
[C][F]=
where each element of [C][F] comes from multiplying a row of [C] with a column of [F].
Example: First element is product of first row and first column.
.
.
.
Now that we have [C][F], we can subtract it from [B], element by element,
[B]-[C][F]=
[B]-[C][F]=
.
.
.
If this is not how the matrices look,please re-state the problem and be more specific about the make up of the matrices (rows x columns).
Here's an example.
[A] is a 2x2 matrix. A=[1,2,3,4].
The assumption is that [A] looks like this,
[A]=
[B] is a 3x2 matrix. B=[5,6,7,8,9,10]
[B]=
Answer:
B and E
aka
E-F and E-D
C-B and C-D
Step-by-step explanation:
Answer:
On the x- axis
Step-by-step explanation:
A) 2(1+2c)
2+4c = 2+4c
B) 6(14r-2t)
= 84r-12t